FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE PADA ANAK BALITA DI PUSKESMAS BINTAUNA KABUPATEN BOLAANG MONGONDOW UTARA - Jon W. Tangka; Rizqa Alamri; Joice Mermy Laoh (Jurnal Ilmiah Perawat Manado (Juiperdo), 2014)
Based on global estimates around 1.8 million people died from diarrheal disease and 90% of them are children under five years and many occur in developing countries. Diarrhea is a collection of symptoms resulting from several factors, such factors as water supply, personal hygiene, and the knowledge factor, but how large proportions and do not clearly known. The purpose of this study was to identify factors associated with the incidence of diarrhea in Public health centers North Bolaang Mongondow Bintauna. The method used is descriptive analytical cross-sectional study design. In 50 samples with data collection conducted by questionnaire. Furthermore, the data that has been collected is processed and presented in the form of a frequency distribution table. Bivariate statistical analysis by chi-square test with a significance level of alfa 0.05. Results, there is a significant relationship between knowledge factors with the incidence of diarrhea ( p = 0.000 ) , water supply factors with the incidence of diarrhea (p= 0.001), and hygiene factors with the incidence of diarrhea (p=0.003). Conclusion: factor knowledge, provision of clean water and personal hygiene significantly associated with the incidence of diarrhea. Suggestion: Increase the frequency of health education to parents/ community, held training on diarrheal disease in the nurses and health volunteers